Reception. (October 2019) - Bridges, Emma; Stead, Henry
Abstract : As the editors of Once and Future Antiquities point out in their preface, 'science fiction, fantasy, and the classics have in common the effect of inviting us to reconsider (by speculating, by imagining, by contextualizing) our own world anew' (xi). The fourteen wide-ranging chapters in this volume eloquently illustrate this point. Contributors explore the multiple ways in which the genres of science fiction and fantasy (SF&F) engage with, respond to, and cast new light on cultural artefacts, story patterns, and characters from the ancient Greek and Roman worlds, reflecting too on how these receptions respond to contemporary preoccupations. Appropriately for a volume on classical receptions, the contributions are all linked by the unifying theme of 'displacements' – a concept which refers here both to the movement of ideas, texts, and themes across time and space, and to the disruption of perceived genre boundaries or preconceived ideas about the relationship between receiving and source texts or cultures.